Spatial genetic structure reveals migration directionality in Mediterranean Ruppia spiralis (Western Sicily) - Bossaer, Laura; Beirinckx, Lise; Sierens, Tim; Mannino, Anna M.; Triest, Ludwig (Frontiers in Marine Science, 2022)
Mediterranean salinas, originally built for salt production, function as alternative wetlands. A variety of accompanying lagoon, ditch, and marsh systems are suitable habitats for salt-tolerant submerged macrophytes and often characterized by monospecific beds of Ruppia. Traditionally, birds are considered the main dispersal vector of submerged macrophytes. However, Ruppia spiralis habitats are under marine influence and therefore interference of coastal currents in their connectivity might be expected. In this study, we aim to infer connectivity and spatial patterns from population genetic structures. Using nuclear microsatellite loci, the nuclear ribosomal cistron and chloroplast sequences, we investigated the genetic diversity, genetic structure, and demographic history of 10 R. spiralis populations along a 25-km coastal stretch of western Sicily encompassing a variety of saline habitats. We tested for local fine-scaled structures, hypotheses of regional isolation by distance, and migration directionality. Our results revealed a high degree of allele and gene diversity that was locally maintained by outcrossing. At the regional level, we detected isolation by distance and identified three genetically differentiated clusters, with a significant structure that matches an overall north-to-south unidirectional migration model. This directionality follows the main sea current, hence indicating the importance of hydrological connectivity in regional conservation management. Significant fine-scale spatial structures only emerged in some populations and were absent in the ‘salina fridda’ habitat that showed the largest clonal richness. The local site-dependent patterns emphasize a need to examine the influence of disturbances on seed recruitment and clonal growth over small distances.